2013
DOI: 10.1086/673868
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Modulation of Testosterone during Breeding of the Rufous-Collared Sparrow (Zonotrichia capensis australis) in Southern Patagonia

Abstract: The roles of testosterone (T) during reproduction are often complex and vary among and within vertebrate taxa and locations, making general hypotheses relating T to breeding behavior and success difficult to integrate. In birds, T is thought to influence degrees of territoriality and associated aggression in males to maximize breeding success. Importantly, most work supporting these ideas has been conducted in the Northern Hemisphere. However, accumulating work on tropical species has shown divergent patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For example, several studies have suggested that playback alone is insufficient to bring about T elevation in circulation (Cramer, 2012; Dufty and Wingfield, 1990; Fokidis et al, 2011; Wingfield and Wada, 1989), and other studies have reported that the use of taxidermic mounts versus live decoys can influence the strength of hormonal responses to STI (Scriba and Goymann, 2008; Scriba and Goymann, 2010). The timecourse of STIs has also varied among studies: Most studies analyze hormonal responses within approximately 30 min of the beginning of the intrusion, but latencies from STI initiation to hormonal sampling have varied from roughly ten minutes to over two hours (Addis et al, 2013; Landys et al, 2007; McGlothlin et al, 2008; Moore et al, 2004a; Van Duyse et al, 2004; Wikelski et al, 1999; Wingfield and Wada, 1989), leaving null results open to the criticism that hormone levels may not have been assessed at the appropriate time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have suggested that playback alone is insufficient to bring about T elevation in circulation (Cramer, 2012; Dufty and Wingfield, 1990; Fokidis et al, 2011; Wingfield and Wada, 1989), and other studies have reported that the use of taxidermic mounts versus live decoys can influence the strength of hormonal responses to STI (Scriba and Goymann, 2008; Scriba and Goymann, 2010). The timecourse of STIs has also varied among studies: Most studies analyze hormonal responses within approximately 30 min of the beginning of the intrusion, but latencies from STI initiation to hormonal sampling have varied from roughly ten minutes to over two hours (Addis et al, 2013; Landys et al, 2007; McGlothlin et al, 2008; Moore et al, 2004a; Van Duyse et al, 2004; Wikelski et al, 1999; Wingfield and Wada, 1989), leaving null results open to the criticism that hormone levels may not have been assessed at the appropriate time.…”
Section: Introductionmentioning
confidence: 99%